PENGARUH PENGGUNAAN METODE PEMBELAJARAN BLENDED LEARNING TERHADAP HASIL BELAJAR IPA PESERTA DIDIK KELAS V DI SDN CIBUNTU 01 - Mutiara Syafitri; Yulia Rahmadhar (PIONIR: JURNAL PENDIDIKAN, 2022)
The world of education is currently facing the Covid-19 pandemic, so education practitioners have begun to develop online learning combined with face to face learning to maximize student learning outcomes. The purpose of this study was to determine whether or an effect of using blended learning methods on science learning outcomes for fifth grade students at SDN Cibuntu 01. This study used a quantitative experimental approach with a quasi-experimental design method, the model The Nonequivalent Control Group Design. The sampling technique used is a cluster sample, which is selected by 25 students as the control class and 27 students as the experimental class. The instrument in this study is multiple choice. Based on the results of the control, the value of Tcount = 3.90 > Ttable = 1.67 and in the experimental class Tcount = 13.27> Ttable = 1.68, so Ha is accepted and H0 rejected. So it can be concluded that there is a significant difference in the results of the pretest and posttest after learning the blended learning method and the conventional method with the average value of students, after learning with the blended learning method is higher than the posttest average after conventional learning.